Despite Our Different Social Identities, We Can Co-Exist: Intergroup Positive and Negative Contact - Abbas Türnüklü; Veysel Karazor; Tarkan Kaçmaz (Anı Publishing, 2019)
The aim of this study was to develop an in-depth understanding of the positive and negative contact experiences among the university students with different social identity categories living in the same dormitory room. The research was designed as a qualitative study utilizing phenomenological approach. A total of 45 students, who identified themselves as Turkish (22) and Kurdish (23) in terms of ethnic and cultural sub-identities were interviewed and qualitative data were collected. In the study, semi-structured interview technique was used to collect data. In the analysis of qualitative data, data reduction, data display and outcome verification steps were followed. The results of the study revealed that the students sharing the same dorm room were generally satisfied with their interactions and had frequent contact. It was also determined that the students were able to get help from each other to a large extent and as much as they could. However, it was ascertained that students refrained from discussing political issues on social identity. It was concluded that, depending on the quality of contact between groups, prejudice between the groups gradually decreased, and in close friendships the human identity and personal characteristics were taken as reference. In addition, it was also observed that as contact between groups becomes negative, social identities become more visible and pronounced. It was determined that a significant number of students were not disturbed by each other in their interactions and did not feel any anxiety. Students began to feel uncomfortable and anxious when political issues based on personal characteristics and social identities were discussed. It was stressed, albeit not as strongly, that students' social identity-based prejudice transformed positively as a result of the frequency and quality of increased social contact.